Knowledge integration in Indonesian state islamic institutes and universities: a review - Toisuta, Hasbollah; Ernas, Saidin; Lampong, Sri Ratna Dewi (Penerbit Universiti Kebangsaan Malaysia, 2024)
Over the last two decades, Islamic state universities in Indonesia have encouraged the idea of integration between Islamic sciences and modern science. However, it can be seen factually that this idea still faces various complex problems. This study aims to describe the paradigms, concepts and science integration programs that have been developed, and what are the implications of scienti>ic integration idea for science and technology products in Islamic universities. The research method used is a qualitative method with a phenomenological approach that combines >ield and library research. This study found that the idea of scienti>ic integration which has been campaigned by Islamic state universities in Indonesia has not yet found an ideal paradigmatic form, and based on the study of this phenomenon, there are two >indings that can be noted